On the Neotropical spider Subfamily Masteriinae (Araneae, Dipluridae) - Passanha, Victor; Brescovit, Antonio D. (Zootaxa, 2018)
The Neotropical species of the diplurid subfamily Masteriinae are revised and redefined. Masteriinae now comprises four genera, Masteria L. Koch, 1893, Striamea Raven, 1981, a new genus, Siremata n. gen. and Edwa Raven, 2015, a fossil genus. The type species, Masteria hirsuta L. Koch, 1893, was used as basis for comparison and the knowledge of the genus has increased. Twelve species of Masteria are redescribed and eight new species are described: M. amarumayu n. sp. and M. mutum n. sp., from Brazil; M. yacambu n. sp., from Venezuela; M. sabrinae n. sp., from Martinique; M. tayrona n. sp., from Colombia; M. aguaruna n. sp., from Peru, M. soucouyant n. sp., from Trinidad and Tobago; and M. galipote n. sp., from the Dominican Republic. Females of Masteria aimeae (Alayón, 1995) and M. golovatchi Alayón, 1995 are described for the first time. Females of M. spinosa (Petrunkevitch, 1925), M. petrunkevitchi (Chickering, 1964), M. lewisi (Chickering, 1964), M. barona (Chickering, 1966), M. downeyi (Chickering, 1966), M. simla (Chickering, 1966), M. colombiensis Raven, 1981 and M. pecki Gertsch, 1982 are illustrated for the first time and rediagnosed. Masteria tovarensis (Simon, 1889) and M. cyclops (Simon, 1889) are synonymized with M. lucifuga (Simon, 1889). Masteria modesta (Simon, 1892) is considered as species inquirendae and M. emboaba Pedroso, Baptista & Bertani, 2015 is considered as incertae sedis, as the type is lost. Both species of Striamea are revised and redescribed. A new genus, Siremata n. gen., is described and includes three Amazonian species: S. valteri n. sp., S. juruti n. sp., S. lucasae n. sp. Knowledge of the distribution ranges of the Neotropical Masteriinae are increased.